Breast cancer screening: An outpatient clinic study - Mustafa Girgin; Kazim Duman; Salih Burcin Kavak; Ebru Kavak (Archives of Clinical and Experimental Surgery, 2017)
Introduction: Systematic screening for breast cancer is performed to reduce the current mortality rate and incidence by diagnosing the patients during the early stage and asymptomatic phase of the disease. A high quality screening program may produce a long-lasting decrease in mortality only if the treatment is of an equal standard. Patients and Method: 350 patients’ medical records, including breast physical examinations, age, gender, mammography findings, number of gravidity, parity and abortion, curettage, whether or not there is systemic and endocrinological disease present and pelvic masses were analyzed retrospectively. Result: Most of the patients (91.1%) had no breast pathological findings. 2.6% of patients had fibroadenoma and 4.6% had fibrocystic breast changes exhibited through mammography. One patient was found to have a breast mass. In that patient, tru-cut biopsy revealed infiltrating ducal carcinoma. Conclusion: A multidisciplinary cancer screening program should be maintained. With such a process, the aim is to reduce the morbidity and mortality of the disease without adversely affecting the health conditions of asymptomatic individuals based on the screening. Success is brought about by the combination of individual features. [Arch Clin Exp Surg 2017; 6(1.000): 23-27]